Investigation of buffer layer parameters for underwater wideband antenna: article / Mariam Mat Saad - Mat Saad, Mariam (2016)
Underwater wireless systems require highly efficient underwater antennas to realize high data rate communication between underwater nodes. This paper presents a study on bufferequipped underwater wideband antennas to realize high speed underwater wireless transmission. Since most underwater environments are lossy mediums affecting the characteristics of conventional antennas, a buffer-layer configuration is considered. In this study, the proposed buffer layer parameters was in terms of the relationship between its dielectric constant and conductivity and RF characteristics of the antenna, by means of 3Delectormagnetic simulation. A microstrip circular patch ultra wideband (UWB) antenna operating at 500 MHz was used as the base antenna, to provide wider bandwidth capability for underwater communication, as most researchers only concentrate on narrow bandwidth. This study proposes buffer layer, with dielectric constant value calculated using geometric average formula. Simulation results indicated that the proposed formula produced the best return loss at 500 MHz.